Development of optimised protocols for paediatric whole-body computed tomography examinations: a figure-of-merit approach - Jacob Leonard Ago; Stephen Inkoom; Benard Ohene-Botwe; Alise Larsen; Ingerd Skaaret Berg (BMC Medical Imaging)
Abstract Background Whole-body computed tomography (WBCT) technique involves higher radiation doses, resulting in increased stochastic health risks, especially when used for paediatric patients. Hence, protocol optimisation is recommended to maximise its benefit-risk ratio, with several available strategies to achieve it. This study used the figure-of-merit (FOM) approach to develop optimised protocols for paediatric WBCT examinations. The rationale is to enhance diagnostic accuracy while minimising radiation exposure, ultimately improving patient safety and outcomes for paediatric patients undergoing WBCT. Methods Newborn and child (5-year-old) anthropomorphic phantoms were scanned with different scan protocols and evaluated for dose and image quality using the CT-Expo and ImageJ programs, respectively. The protocols for trunk examinations were divided into arterialphase-only and combined arterial and venous phase to develop appropriate protocols based on patients’ initial focused assessment with sonography for trauma (FAST) results. The protocols with the highest FOMs were selected as the best optimised protocols. Results The estimated WBCT ED (WBED) for the optimised protocols ranged from 2.6 mSv to 5.8 mSv with estimated FOM of 3.83 to 59.35. The mean effective doses (EDs) for newborn and child arterial phase-only protocols were not significantly lower than the combined arterial and venous phase protocols (p = 0.069, 0.082 respectively), while the mean signal-to-noise ratio of the combined phase protocols for newborn and child phantoms were insignificantly higher than the single-phase protocol (p = 0.089, 0.662 respectively). Conclusion The estimated EDWB from this study were lower than established values. The selected protocols are recommended for newborns and children (1–7 years) using the GE Revolution CT and Siemens SOMATOM Definition Edge CT scanners.